Analysis of Customer Interest in Using the Digital Sharia Pawnshop Application in Terms of Technology Acceptance Model in Sharia Pawnshop Alaman Bolak - Hotman Pandapotan; Arbanur Rasyid; Abdul Nasser Hasibuan (Universitas Muhammadiyah Surabaya, 2023)
This research is motivated by a phenomenon where Pegadaian Syariah CPS Alaman Bolak customers are still not interested in using the PSD application, besides that a sense of trust that is more dominant when transacting directly to Pegadaian outlets than using the PSD application is also the cause of the few application users and there are still many who do not know the use of the PSD application. The purpose of this study is to determine how the effect between convenience, usefulness and trust on customer interest in using the PSD application is moderated by knowledge. This research is a quantitative study with a sample size of 157 samples. The data collection instrument was carried out by conducting structured interviews with each respondent by providing a questionnaire to fill in. Data analysis uses outer model, inner model and hypothesis testing for each variable studied. Based on the results of the study, it is known that there is an influence between the ease of using the PSD application on customer interest. There is no influence between the usefulness of using the PSD application on customer interest. There is an influence between trust using the PSD application on customer interest. There is no influence between the usefulness of using the PSD application on customer interest. There is moderation of knowledge on the effect of ease of using the PSD application with customer interest. There is no moderation of knowledge on the effect of the usefulness of using the PSD application with customer interest. There is no moderation of knowledge on the effect of trust in using the PSD application with customer interest in Sharia Pownshop Alaman Bolak Branch.